42.1k views
3 votes
Use completing the square to solve for x in the equation 2x^2-5x+1=3

User Shaheem
by
5.5k points

2 Answers

5 votes

Answer:

x =
(5)/(4) ±
(√(41))/(4)

Explanation:

First, set the equation to equal zero.

2x^2-5x+1=3
-3 -3

2x^2-5x-2=0
Then, divide the equation by the coefficient of a (the value associated with
x^2) to equate a to 1.

(2x^2-5x-2=0)/(2)

x^2-(5)/(2)x-1=0
Next, identify the b in this equation. In quadratic form, it is the middle term with the x. Currently, the b equals
-(5)/(2)x. To create a perfect square trinomial, we must divide b by 2, then add the square of it to the equation.

-((5)/(2))/(2)=-(5)/(4)

x^2-(5)/(2)x+(-(5)/(4))^2-1=0
But you cannot simply add to an equation as that changes the fundamental truth of said equation. Therefore, we must also subtract
(-(5)/(4))^2 from each side.

(-(5)/(4))^2 = (25)/(16)

x^2-(5)/(2)x+(-(5)/(4))^2-1-(25)/(16) =0
Now we can isolate our perfect square trinomial to the left side of the equation, then convert it to a squared binomial.

x^2-(5)/(2)x+(-(5)/(4))^2-(41)/(16) =0
+
(41)/(16) +
(41)/(16)

x^2-(5)/(2)x+(-(5)/(4))^2 =(41)/(16)

(x-(5)/(4))^2 =(41)/(16)
We can say we have properly completed the square now that we have our squared binomial. To solve this, we just have to isolate the x by taking the square root of each side and using the inverse operation of any constant on the x side.

x-(5)/(4) = ±
\sqrt{(41)/(16)}
+
(5)/(4) +
(5)/(4)
x =
(5)/(4) ±
\sqrt{(41)/(16)}
The square root of 16 is 4, so our final answer is...
x =
(5)/(4) ±
(√(41))/(4)
Which, if you're asking this due to Edge, is D.

User Flakomalo
by
6.3k points
2 votes

Answer: did this help

Use completing the square to solve for x in the equation 2x^2-5x+1=3-example-1
User Arabasta
by
5.2k points